Elections in the Municipality of Novi Pazar in the Early 1990s - Minić, Ratko S. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The fall of the Berlin Wall led to the collapse of socialism and initiated the process of re-parliamentarization. This period was characterized by the establishment of multi-partyism, involving the revitalization or transformation of some old parties and the formation of new parties. Additionally, multi-party elections were organized.The path of political pluralization of SR Serbia started after the adoption of the position of the LC of Serbia at the XI Congress that "the League of Communists does not claim a political monopoly". Party pluralization and political processes in the territory of the Novi Pazar municipality followed the above processes and events. During 1990, committees of the most important republican parties (Socialist Party of Serbia, SPS, Serbian Renewal Movement, SPO, Union of Reform Forces of Yugoslavia, SRSJ, and others) were founded in the municipality, along with a branch of the most significant party from the SR Bosnia and Herzegovina, the Party of Democratic Action, SDA. The antagonism between the peoples at the federal level was transferred to the municipal area as well. Different views of socio-political events from the past in the municipality contributed to increased divisions. Due to the political turbulence in the country, the electorate primarily turned to parties with a national program. National parties often emphasized the perceived threat and humiliation of their own national groups in the preceding period. With such statements, parties rapidly carried out national homogenization and division among the local population, also profiting politically.Trust in uni-national parties was immediately evident. During the first multi-party elections, the SDA won convincingly. Its candidates managed to secure 90% of the votes from the local Muslim population. The Serbian population allocated its votes to the SPO and SPS, with the SPO winning the parliamentary elections. The tendency of trust in national parties continued in the following period. The Party of Democratic Action managed to maintain political primacy among the Muslim population of the municipality during this period. This is evidenced by the boycotts of the elections in 1992 and 1993 by the majority of Muslims. A smaller number of Muslims supported more moderate parties, such as the SRSJ. The Serbian population of the municipality, unlike the Muslim population, actively participated in all elections. Throughout the entire period, the political pluralization of the Serbs was noticeable. The Socialist Party of Serbia managed to assert itself over time as the most significant party among the local Serbian population.The elections showed that the politics of moderate and more conciliatory currents, such as SRSJ, experienced a debacle. Despite the antagonisms and the tense political climate, the elections took place in a tolerant manner without major incidents. The election results were accepted. An enviable amount of political culture was demonstrated among the local parties. Democratic elections have shown that it is possible to discuss very delicate and latent problems from the past, even in difficult times.With the de-escalation of the situation at the level of Yugoslavia and, subsequently, with the changes on October 5th, inter-ethnic relations in political advancements began to lose their importance. Gradually, tensions subsided. Political pluralization among the Muslim population of the municipality also contributed to this. Instead of national issues, the municipality's focus shifted to the daily life concerns of the local population and the inter-party relations of the Muslim parties.
Keywords: elections; Raška area; Sandžak; Novi Pazar; Party of Democratic Action (SDA); Socialist Party of Serbia (SPS); Serbian Renewal Movement (SPO)